Faktor-Faktor yang Berhubungan dengan Perilaku Seksual pada Remaja Di SMKN 1 Painan Tahun 2020 - Yuliva Yuliva; Elda Yusefni; Vini Azian (Jurnal Sehat Mandiri, 2020)
Based on the result of SDKI in 2012 and 2017 there was an increase of adolescent sexual behavior, the proportion of female adolescents that had sexual intercourse before marriage 1% became 2%. The purpose of the research was to find out the factors related to sexual behavior on adolescents at SMKN 1 Painan in 2020. The type of the research is analytic with cross sectional design. The research was conducted from November 06, 2019 to June 30, 2020. The population of the research was the students of SMKN 1 Painan, the sample number was 85 students. The data collection used questioner with google form. The data processing technique was editing, coding, entry, tabulating and cleaning. The data analysis was univariate and bivariate with chi square statistical test. The result of univariate analysis was 54,1% respondents had risky sexual behavior, low religiosity 45,9%, authoritarian parenting 36,5%, and peers play a role in sexual behavior 54,1%. The result of bivariate analysis for religiosity relationship was p=0,001 (p<0,05), parenting style relationship with the value p=0,000 (p<0,005) and peer role p=0,026 (p<0,005) with the sexual behavior on adolescents. It was cocluded that there was the relation of religiosity, parenting style and peer role with the sexual behavior on adolescents. It is expected that the school activates PIK-R at school in order that adolescents have a place to get correct information about adolescents reproductive health and sexuality.